2017
DOI: 10.1159/000476074
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Activation in Chronic Kidney Disease: Role of Uremic Toxins

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor involved in the expression of xenobiotic-metabolizing enzymes, inflammatory cytokines and adhesion molecules. Uremic toxins such as indoxyl sulfate and indole acetic acid are derived from tryptophan fermentation by gut microbiota; they accumulate in patients with chronic kidney disease (CKD) on haemodialysis and have recently emerged as potent ligands of AhR. Therefore, AhR can serve as a mediator in inflammation and cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 57 publications
0
56
0
Order By: Relevance
“…In this previous study, we showed that CYP1B1 expression in peripheral monocytes was increased by the treatment with serum of patients with ESRDs who have higher concentrations of serum IS, and this induction was significantly inhibited by the AhR antagonist GNF351 (N-(2-(1H-indol-3-yl)ethyl)-9-isopropyl-2-(5-methylpyridin-3-yl)-9H-purin-6-amine) (14). In this context, recent studies suggested that AhR activation by IS in the blood of patients with kidney dysfunction has important pathophysiological implications (17,18). The data in the present study further support the idea that accumulated IS in sera from patients with ESRD causes AhR-dependent induction of SOCS2 and leads to a reduction in the level of AhR by degradation of ligand-activated AhR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this previous study, we showed that CYP1B1 expression in peripheral monocytes was increased by the treatment with serum of patients with ESRDs who have higher concentrations of serum IS, and this induction was significantly inhibited by the AhR antagonist GNF351 (N-(2-(1H-indol-3-yl)ethyl)-9-isopropyl-2-(5-methylpyridin-3-yl)-9H-purin-6-amine) (14). In this context, recent studies suggested that AhR activation by IS in the blood of patients with kidney dysfunction has important pathophysiological implications (17,18). The data in the present study further support the idea that accumulated IS in sera from patients with ESRD causes AhR-dependent induction of SOCS2 and leads to a reduction in the level of AhR by degradation of ligand-activated AhR.…”
Section: Discussionmentioning
confidence: 99%
“…Since IS was identified as a potent endogenous ligand for the aryl hydrocarbon receptor (AhR) (16), an increasing number of studies have focused on the biologic role of the AhR pathway in the pathogenesis of CKD (13,(17)(18)(19). However, the mechanisms underlying the IS-mediated AhR pathway have mainly been explored in renal cells, vascular endothelial cells (VECs), and vascular smooth muscle cells.…”
mentioning
confidence: 99%
“…The product of tryptamine degradation IAA (synonyms: beta-Indolylacetic acid, indolylacetic acid) is also a TrpRS inhibitor [ 46 ] although less potent than tryptamine. IAA is a uremic toxin derived from Trp fermentation by gut microbiota; it accumulates in patients with chronic kidney disease on haemodialysis [ 77 ]. IAA upregulates the eight genes regulated by the transcription factor aryl hydrocarbon receptor (AHR) [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…82 The AHR is a prominent transcriptional regulator of CYP1A1, 60 and is potently activated by gut-derived protein-bound uremic toxins which accumulate in plasma and tissues in AKI and CKD. 62,63,83,84 This activation is linked with the vascular dysfunction and systemic inflammation of CKD. 62,[85][86][87] In our study, these toxins were increased in urine of SCS pigs, potentially linking to the inflammatory pathways of SCS.…”
Section: Discussionmentioning
confidence: 99%